The planktonic microbiome of the Great Barrier Reef - Steven Robbins; Marko Terzin; Katherine Dougan; Julian Zaugg; Sara C. Bell; Patrick W. Laffy; J. Pamela Engelberts; Kim-Anh Lê Cao; Renee K. Gruber; Nicole S. Webster; David G. Bourne; Philip Hugenholtz; et al. (Nature, 2026)
Abstract Large genome databases have markedly improved our understanding of marine microorganisms 1–5 . Although these resources have focused on prokaryotes, genomes from many dominant marine lineages, such as Pelagibacter and Prochlorococcus , are conspicuously underrepresented. Here we present the Great Barrier Reef Microbial Genomes Database (GBR-MGD), comprising 5,283 prokaryotic genomes obtained from Great Barrier Reef seawater samples using Nanopore and Illumina sequencing, including a collection of high-quality genomes of underrepresented groups. We show that standard short-read assemblies miss these populations owing to a combination of strain heterogeneity and low-GC-percentage sequencing bias. The GBR-MGD also comprises 20 chromosome-level picoeukaryote and 808,585 viral genomes, including a newly described clade of marine Crassvirales . We demonstrate the utility of the GBR-MGD to identify indicator taxa that can reliably predict the effects of reef management practices, such as the establishment of marine protected zones.